2005
DOI: 10.1002/bsl.593
|View full text |Cite
|
Sign up to set email alerts
|

The problem behavior model: the development of a stalkers clinic and a threateners clinic

Abstract: Traditionally, forensic mental health services have focused on the assessment and treatment of offenders with serious mental disorders. In recent years, there has been growing recognition that forensic clinicians have an important role to play for those offenders who engage in criminal acts driven by psychological or/and social problems, which may, or may not, occur in conjunction with a major mental disorder. This is especially true for specific offenses such as stalking and threatening. This article describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…Skill development programmes for the intellectually impaired, such as positive behaviour support (Carr et al, 2002), are conceived in a more accessible way, but may need to be coupled with specific strategies to manage identified risks for escalation to violence (Gendreau, Little, & Goggin, 1996;Mullen & Ogloff, 2009;Quinsey et al, 2006). It has been our experience that multiple treatment techniques are needed that include challenging the distorted attitudes which have served to justify, minimise or deny the problem behaviour of threatening (Warren et al, 2005).…”
Section: Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Skill development programmes for the intellectually impaired, such as positive behaviour support (Carr et al, 2002), are conceived in a more accessible way, but may need to be coupled with specific strategies to manage identified risks for escalation to violence (Gendreau, Little, & Goggin, 1996;Mullen & Ogloff, 2009;Quinsey et al, 2006). It has been our experience that multiple treatment techniques are needed that include challenging the distorted attitudes which have served to justify, minimise or deny the problem behaviour of threatening (Warren et al, 2005).…”
Section: Treatmentmentioning
confidence: 96%
“…The tests were administered as part of a clinical assessment conducted by a clinical/ forensic psychologist (Warren, MacKenzie, Mullen, & Ogloff, 2005). Administration occurred only when the threateners' consented, they spoke English fluently and they had sufficient literacy to read and understand the tests' instructions and questions.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Although previous reports have described treatment approaches for stalking offenders (Mullen, Pathé, & Purcell, 2000;Warren et al, 2005), none have reported any effectiveness data. Despite the small, non-randomized sample, participants who completed treatment were significantly less likely to re-offend compared to either those who failed to complete treatment or published recidivism data (Rosenfeld, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, training the medical staff and law enforcement professionals about stalking behaviour and the particular needs of stalking victims may be a promising approach [55]. Therapeutic interventions directed to the stalking behaviour itself primarily focus on a problem-behaviour model, and in Australia the concept of a specialized stalkers' clinic is currently the subject of scientific evaluation [56]. Considering the high prevalence rates and the tremendous psychosocial and economic consequences of stalking, however, it has to be stated that there is still a formidable lack of scientific research on treatment strategies and intervention programmes.…”
Section: Intervention Strategies For Stalking Behavioursmentioning
confidence: 99%